Evaluation of Operational Performance of Intersection And Optimization of Signal Timing: A Case Study of Mangalgadhi Chowk, Surkhet - Adhikari, Sajana; Marahatta, Ishwor Chandra; Pokhrel, Asmita (Journal of Advanced College of Engineering and Management, 2025)
Surkhet is one of the growing cities in Nepal. The growth in urbanization often results in the growth of traffic congestion along the city. This paper presents a comprehensive evaluation of the operational performance of the Mangalgadhi intersection, Surkhet through SIDRA Intersection 8 software. The analysis focuses on comparing existing traffic conditions with proposed improvements under a left-controlled scenario and signal optimization. Key performance indicators such as Back of Queue (BOQ), level of Service (LOS), and average vehicle delay were analysed across four critical time intervals. The analysis showed that the intersection was functioning with significant delays, queue lengths and poor LOS. Out of two alternatives, left-turn controlled reduced the BOQ up to 39% making it effective measure for improvement of intersection.